Laughter Therapy Card for Sleep Disorder Older Adults in Lubuklinggau City - Dwi Ari Wibowo, Wahyu; Ulfa, Msy Hartina; Wijaya, Sapondra (International Journal of Nursing and Health Services (IJNHS), 2023)
Introduction: Sleep disorders affecting 40 to 70% of older adults manifest sleep disorders. Compromised sleep detrimentally impacts older adults, leading to daytime sleepiness, heightened fall risks, and cognitive decline. Demonstrates promising therapy in enhancing sleep quality and reducing fatigue through laughter therapy cards. Objective: The study aimed to construct and test the effect of laughter cards on improving the sleep quality of old adults in Lubuklinggau City, South Sumatra, Indonesia. Method: This quantitative study was conducted with a quasi-experimental approach. A total of 32 participants took part in this study, of which 32 participants attended laughter therapies with laughter therapy cards in 1 month by doing activities in laughter therapy four times in 1 month, each 45 minutes, before and after laughter therapies are assessed by PSQI score. The Cronbach's alpha coefficients used were 0.81. The paired t-test was used to determine the data statistically. Result: Before and after therapies showed different values of PSQI score. PSQI score of older adults before treatments (10.50), became (7.68) after therapies, and had a statistically significant p 0.001. Recommendation: Continuous laughter therapies are non-pharmacological therapy for older adults with a sleep disorder